THE EFFECT OF RECOGNIZING STUDENTS' LEARNING STYLES TO MINIMIZE DIFFICULTIES IN LEARNING - Rista Apriliya Devi; Salsabila Liliyani (Universitas Muhammadiyah Lamongan, 2024)
This research is motivated by the lack of recognition and understanding of teachers, students, and parents regarding various types of student learning styles. In addition, this research also aims to provide knowledge about the effect of learning style recognition on learning achievement to teachers, students, and even parents. The research method used is a literature study in which the author examines various journals, books, articles, theses, and previous studies on the influence of learning styles and learning difficulties. Based on the results of this study, it can be concluded that the efforts that can be made by teachers, students, and parents in recognizing learning styles have a big influence on improving student achievement.